Identifying humor in stand-up comedy: A preliminary study - Wawrzyniuk, Justyna (LingBaW. Linguistics Beyond and Within, 2021)
This paper describes a preliminary study examining how the audience of stand-up comedy approach humor analysis. By expanding the scope of the General Theory of Verbal Humor (Attardo 2001), it was possible to use the framework to aid and systematize the interpretation process, resulting in shifting the theory’s focus from humor production to humor perception. The first part of the paper introduces the main premise of stand-up comedy. The second part is devoted to the theoretical aspects, namely the theory of humor. The third part discusses the methodology of the preliminary study: a two-step interpretation task done by four audience members. The fourth and the fifth sections present the results of the study and discuss the implications. The outcome of the analysis gives an understanding as to what the audience may focus on during the interpretation process, which allows for identification of differences in humor perception.